Effect of using wall media and students’ learning styles on volleyball lower passing abilities of tenth-grade students - Bambang Sumedi; M. Rufi’i; Yoso Wiyarno (Kreasi Teknologi Informasi, 2020)
This study aims to investigate the effect of using walls as media and learning styles on ability to pass of the tenth-grade students’ ability of SMAK Suropati Sidoarjo and SMA Santo Yusup Surabaya. A total of 120 tenth-grade students of both high schools were the study subjects devided into the experimental and control groups. A pre-test post-test design randomnized control group design was employed. To collect the data, the volleyball passing tests were taken by the students. A two-way ANOVA and tests of homogeneity and normality were used to analyze the data. The results showed that the significant test results accepted the alternative hypothesis. It means that there was a significant effect and no interaction training using the wall vs. non-walls as media and learning styles on the lower pasing ability of the tenth-grade students of SMAK Suropati Sidoarjo and SMA Santo Yusup Surabaya.